Direct Parabrachial–Cortical Connectivity. (8th May 2020) - Grady, Fillan; Peltekian, Lila; Iverson, Gabrielle; Geerling, Joel C
Abstract: The parabrachial nucleus (PB) in the upper brain stem tegmentum includes several neuronal subpopulations with a wide variety of connections and functions. A subpopulation of PB neurons projects axons directly to the cerebral cortex, and limbic areas of the cerebral cortex send a return projection directly to the PB. We used retrograde and Cre-dependent anterograde tracing to identify genetic markers and characterize this PB–cortical interconnectivity in mice. Cortical projections originate from glutamatergic PB neurons that contain Lmx1b (81%), estrogen receptor alpha (26%), and Satb2 (20%), plus mRNA for the neuropeptides cholecystokinin ( Cck, 48%) and calcitonin gene-related peptide ( Calca, 13%), with minimal contribution from FoxP2+ PB neurons (2%). Axons from the PB produce an extensive terminal field in an unmyelinated region of the insular cortex, extending caudally into the entorhinal cortex, and arcing rostrally through the dorsolateral prefrontal cortex, with a secondary terminal field in the medial prefrontal cortex. In return, layer 5 neurons in the insular cortex and other prefrontal areas, along with a dense cluster of cells dorsal to the claustrum, send a descending projection to subregions of the PB that contain cortically projecting neurons. This information forms the neuroanatomical basis for testing PB–cortical interconnectivity in arousal and interoception.